What is Political literature? Adorno and Marxist Aesthetics: הקדמה למסה "מעורבות" - Banbaji, Amir (MiKAN, 2008)
This article explores some of the main tenets of Theodor Adorno’s aesthetic theory. As an introductory essay to Hebrew translation of Adorno’s 1962 "Commitment", the article is mainly concerned with his complex understanding of the nature of the political in artistic production. Following a brief elucidation of the dialectical nature of his writing, the article situates Adorno’s definition of the political vis-a-vis with that of his main opponents, j. p. Sartre, Georg Lukacs, and Bertolt Brecht. The article then attempts to anchor this quadruple constellation in Adorno’s moral and epistemological commitment towards the "non-identical," as well as his defiance of the existentialist "jargon of authenticity." It is suggested that Adorno’s philosophical "obligation toward the object" (as it is stated in "Commitment" and elsewhere in his writings) is replicated in his literary theory, thus producing a fascinating call for a negative literary knowledge of the world, as well as a non-thematic politicization of the literary work. Thus, Adorno’s theory provides a specific alternative to Lukacs and Brecht’s realism on the one hand and Sartre’s existentialist stance towards literature on the other. The essay ends with a discussion of Adorno’s relevance to theoretical issues tackled by contemporary Hebrew literary critics. In this context a question is raised regarding the relevance of Adorno’s injunction against writing poetry after Auschwitz. To what extent is Adorno’s famous statement compatible with the post-Holocaust attacks aimed at the classical works of Sh.Y. Abramovich’s (Mendele the Book-Peddler)? An "Adornian" reading of Abramovich’s representation of the Shtetl, it is suggested, could be a way out of the bind.